B-emission Stars in Southern Sky Observed in Bosscha Observatory: Spectroscopic Study of HÎ± Spectral Line Variability - Aprilia, Aprilia; Malasan, Hakim Luthfi; Ramadhania, Geavani Eva; Jatmiko, Agus Triono Puri; Irfan, Mochamad; Ramadhan, Dhimaz Gilang; Istiqomah, Ade Nur; Akbar, Evan Irawan (Journal of Mathematical and Fundamental Sciences, 2019)
HÎ± line variations of 8 B-emission (Be) stars are presented. Stars that are listed in the Bright Star Catalogue were observed in 2009 at the Bosscha Observatory, Lembang, Indonesia. It was found that 4 stars showed phase changing from Be double-peaked to Be single-peaked emission line profiles, 1 showed single-peaked to double-peaked profiles, 1 showed double-peaked to B-normal, while two other stars did not show phase changing. The stars also showed variations in the V/R and E/C values, which represent the strength of the emission lines. The phase changes were detected from a comparison of the observed data to the current data in the BeSS database.